Analytical study of global solar radiation and climate data for solar energy system applied at south of Libya (Sebha University Conference Proceedings, 2024)
Increasing of the energy demand and the global concern about preserving the environment using fossil fuels has led to the use of environmentally friendly renewable energies. The most reliable renewable energy is solar energy. It is an abundant and practically limitless source of energy. This paper conducts a statistical analysis of solar radiation and the impact of other weather factors on it. The solar radiation is an important factor in determining or designing solar energy systems. We analyzed a data of four cities located in western, eastern, northern and southern Libya. Microsoft Excel used to conduct this analysis and simulated 1 kWp of PV modules by SAM software for the four cities to know the amount of its annual productivity. Comparison and statistically analysis between them are in terms of global solar radiation, relative humidity and temperatures. The results showed that the city of Sebha has the highest average daily solar radiation compared to other cities with the strongest annual productivity reaching 1833 kWh/kWp year. Which makes it more amenable to a solar energy system.